Competitive marketing in tourism [videorecording] - Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2009)
A case study of Mt Hotham resort in the Victorian Alps as an illustration of how branding and marketing influences the way people make tourism decisions
Executive producer, Simon Garner
Voice over : Adam Mattaliano
Subtitle available in English
Keywords: Tourism -- Marketing -- Australia -- Alpine regions (Vic.); Interpersonal relations; Hospitality industry -- Employees